Pengaruh Model Pembelajaran Kooperatif Metode Cooperative Script Terhadap Hasil Belajar PKN di Kelas III SD Negeri 101961 Timbang Deli - Herdyana, Thessa; Hidayat, Wahyu (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2023)
This thesis aims to determine the cooperative script method to obtain student learning outcomes, the effect of the cooperative script method on the learning outcomes of third grade Civics students at SD Negeri 101961 Timbang Deli in the 2022/2023 academic year. The method used is quantitative research. The data collection methods used are observation, tests and documentation. The sample in this study amounted to 20 experimental class students and 20 control class students. The results of research and discussion show the calculation result of -7.464 compared to the significant level of r table 5% N = 20 of 0.444, it can be concluded that it is concluded that the hypothesis (Ho) is accepted (Ha is rejected). Analysis using pretest and post-test. By doing a pretest in the experimental class there was 1 respondent with a high percentage of 5%, 12 respondents with a low percentage of 60%, 7 respondents with a very low percentage of 35%. While the posttest in the experimental class consisted of 13 respondents with a very high percentage of 65%, 7 respondents with a high percentage of 35%. with a high percentage of 5%, 12 respondents with a low percentage of 35%.